2006
DOI: 10.1037/0012-1649.42.6.1069
|View full text |Cite
|
Sign up to set email alerts
|

Visual processing and infant ocular latencies in the overlap paradigm.

Abstract: Young infants have repeatedly been shown to be slower than older infants to shift fixation from a midline stimulus to a peripheral stimulus. This is generally thought to reflect maturation of the neural substrates that mediate the disengagement of attention, but this developmental difference may also be attributable to young infants' slower processing of the midline stimulus. This possibility was tested with 3- and 7-month-old infants in 2 experiments in which the degree of familiarity of the midline stimulus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 39 publications
4
36
1
Order By: Relevance
“…Field's hypothesis was based on the finding that preterm children showed more gaze aversion than full term children, even when the amount of stimulation the children received was controlled for, suggesting that preterm children possibly need longer and more frequent gaze aversion to process the same amount of information. Our data cannot fully confirm this hypothesis, as our attention measure was not designed to assess Gaze aversion in preterm infants 22 information processing abilities (Blaga & Colombo, 2006), although visual attention is assumed to be one part of information processing (Rose et al, 2009).…”
Section: Gaze Aversion In Preterm Infants 20contrasting
confidence: 50%
“…Field's hypothesis was based on the finding that preterm children showed more gaze aversion than full term children, even when the amount of stimulation the children received was controlled for, suggesting that preterm children possibly need longer and more frequent gaze aversion to process the same amount of information. Our data cannot fully confirm this hypothesis, as our attention measure was not designed to assess Gaze aversion in preterm infants 22 information processing abilities (Blaga & Colombo, 2006), although visual attention is assumed to be one part of information processing (Rose et al, 2009).…”
Section: Gaze Aversion In Preterm Infants 20contrasting
confidence: 50%
“…Instead, looking patterns are used to gain insight into how infants allocate their attentional resources and the neural substrate of these mechanisms. Findings from these studies have indicated that infants take longer to process stimuli and have more problems disengaging from stimuli early in the first year of life Blaga & Colombo, 2006;Colombo, 2002;Hood, 1995;Hood & Atkinson, 1993). Towards the end of the first year, infants start to actively engage in more interesting stimuli, whereas they lose interest in less dynamic displays (Courage et al, 2006), a phenomenon that Colombo (2002) has interpreted as the emergence of endogenous or sustained attention.…”
Section: Looking Behaviour As a Measure Of Infant Cognitionmentioning
confidence: 99%
“…Such competition effects have been shown to exist from as early as 2 to 3 months of age, though they tend to decrease with age (Blaga & Colombo, 2006;Dannemiller, 1998Dannemiller, , 2000.…”
Section: Findings At the Group Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Within developmental psychology, ''attention'' is currently studied with respect to several different (but potentially deeply related, see Posner & Rothbart, 2007) phenomena, including sustained attention (e.g., Miller, Ables, King, & West, 2009;Richards, 2005Richards, , 2008, attentional switching and disengagement (e.g., Blaga & Colombo, 2006;Posner, Rothbart, Thomas-Thrapp, & Gerardi, 1998;Richards, 2008), executive control (e.g., Chatham, Frank, & Munakata, 2009;Diamond, 2006;Hanania & Smith, in press), and joint attention among social partners (e.g., Grossmann & Farroni, 2009;Hirotani, Stets, Striano, & Friederici, 2009). There are very few developmental studies specifically concerned with contextually cued attention (e.g., Goldberg, Maurer, & Lewis, 2001;Smith & Chatterjee, 2008;Wu & Kirkham, in press).…”
Section: Cued Attentionmentioning
confidence: 99%